Cardiovascular adverse events in modern myeloma therapy - incidence and risks: a review from the European Myeloma Network (EMN) and Italian Society of Arterial Hypertension (SIIA) - Bringhen, Sara; Goldschmidt, Hartmut (Haematologica, 2018)
Cardiovascular disease in patients with multiple myeloma may derive from factors unrelated to the disease (age, diabetes, dyslipidemia, obesity, prior cardiovascular diseases), related to the disease (cardiac AL-amyloidosis, hyperviscosity, high-output failure, arteriovenous shunting, anemia, renal dysfunction) and/or related to anti-myeloma treatment (anthracyclines, corticosteroids, alkylating agents, immunomodulatory drugs, proteasome inhibitors). Good knowledge of cardiovascular events, effective dose reductions, prevention and management of early and late cardiovascular side effects of chemotherapeutic agents are essential in current clinical practice. Myeloma experts are obliged to carefully balance the efficacy and toxicity of drugs for each individual patient. This review summarizes current data and novel insights into cardiovascular adverse events of today’s anti-myeloma treatment, focusing on carfilzomib, as a starting point for developing consensus recommendations on preventing and managing cardiovascular side effects in patients with multiple myeloma.
Gesehen am 10.09.2019